The role of agency in the construction and development of professional identity. (2nd January 2023) - Chávez, Jorge; Fauré, Jaime; Barril Madrid, Juan
ABSTRACT: The aim of this article is to achieve greater understanding of the relationship between professional teacher identity and agency. From our perspective, agency is a necessary consequence of the process of construction and development of professional teacher identity. On this basis, we conducted a qualitative study involving analysis of the subjective learning experiences of three future teachers engaged in their final year of training. We analysed these experiences using a previously published analytical model based on the positional changes that occur as a consequence of the evaluation of certain objects that are key to professional identity. Our results allow us to confirm that in the case of subjective learning experiences involving positional changes, agency is key to the consolidation of an enabling professional identity.